Macrophages in sepsis-induced acute lung injury: exosomal modulation and therapeutic potential - Lv, Kaiying; Liang, Qun (Frontiers in Immunology, 2025)
Sepsis-induced acute lung injury (ALI) remains a leading cause of mortality in critically ill patients. Macrophages, key modulators of immune responses, play a dual role in both promoting and resolving inflammation. Exosomes, small extracellular vesicles released by various cells, carry bioactive molecules that influence macrophage polarization and immune responses. Emerging researchers have identified exosomes as crucial mediators that modulate macrophage activity during sepsis-induced ALI. This review explores the role of exosomes in modulating macrophage functions, focusing on the cellular interactions within the lung microenvironment and their potential as therapeutic targets. It highlights the regulation of macrophages by exosomes derived from pathogenic germs, neutrophils, alveolar epithelial cells, and mesenchymal stromal cells. By understanding these mechanisms, it aims to uncover innovative therapeutic strategies for sepsis-induced ALI.